Public Perception of Street Vendors in Pontianak Auditorium Park Tanjungpura University - Hendryan, Hendryan; Chainar, Chainar; Nurwijayanto, Nurwijayanto; Purnama, Desca Thea; Marini, Marini (International Journal of Multidisciplinary Approach Research and Science, 2024)
Business development in the Auditorium Park of Tanjungpura University, especially street vendors, has increased, giving rise to increasingly competitive competition between street vendors. This study aims to describe and analyse the factors of public acceptance of street vendors, the situation of the existence of street vendors and target object factors that influence the emergence and increase of street vendors around the Auditorium Park of Tanjungpura University Pontianak. The method used in this study is a qualitative research method using a descriptive approach-data collection using interviews, observation, and documentation. The data analysis techniques used are data reduction, data presentation and conclusion. The results of this study showed that several factors were found, such as the public acceptance of street vendors who were dominant to an unfavourable view of the existence of street vendors that caused congestion and slums around the Auditorium Park. Then, from the Situation factor, the existence of street vendors makes it irregular, and the scattered garbage creates a shabby impression around the park. The last factor of the target object of street vendors is the park, which is one of the objects, and the presence of visitors or people who gather in the park auditorium to attract street vendors. Suggestions addressed to Tanjungpura University must be given clear regulations and strict action from Tanjungpura University for street vendors selling in Tanjungpura University Auditorium Park so that they are orderly so as not to take the shoulder of the road that hinders the mobility of road users. To the Government, street vendors must be given a unique, strategic and spacious place so that street vendors are free to trade and the city layout is neatly arranged.